2010
DOI: 10.1007/s12284-010-9057-4
|View full text |Cite
|
Sign up to set email alerts
|

Important Sensory Properties Differentiating Premium Rice Varieties

Abstract: In rice-consuming countries, specific varieties are recognized as premium, "gold standard" varieties, while others are recognized as being superior but second best, despite being identical using the current suite of tools to evaluate quality. The objectives of this study were to determine if there are distinguishable differences in sensory properties of premium and second best varieties and whether these differences are common to premium varieties. Color, an important sensory property, was determined on the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 16 publications
5
91
1
2
Order By: Relevance
“…The chemical composition of rice determines its nutritional value and sensory properties such as taste and texture [4,5]. Amylose content in the starch has been identified as one of the main composition components that affect its textural properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of rice determines its nutritional value and sensory properties such as taste and texture [4,5]. Amylose content in the starch has been identified as one of the main composition components that affect its textural properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…A aceitação foi influenciada pelos atributos sensoriais dos grãos cozidos de cada genótipo (Taylor & Duodu, 2009) e confirmou que os brasileiros apreciam arroz cozido com grãos soltos e pouco macios (Ferreira et al, 2005). 'Irga 417' (irrigado) e 'BRS Primavera' (terras altas) são padrões de qualidade das classes "premium" e "superior" respectivamente (Champagne et al, 2010), enquanto AB101002, uma linhagem do sistema de cultivo irrigado, é promissora para o consumo por atender a expectativa do consumidor em relação às características sensoriais de seus grãos cozidos. A aceitação, por estar vinculada às características sensoriais -principalmente as propriedades de textura, associadas às características químicas intrínsecas dos grãos de cada genótipo -não diferiu quanto aos sistemas de plantio.…”
Section: Amido Amilose ----------------------------------------------unclassified
“…A fim de atender as exigências dos consumidores, novos genótipos, específicos para os dois sistemas de cultivo e com alta qualidade agronômica, culinária e sensorial estão em constante desenvolvimento (Brasil, 2015). Exemplos são 'Irga 417' e 'BRS Primavera', com padrões de qualidade "premium" e "superior", respectivamente (Champagne et al, 2010). O estudo, por meio de várias metodologias, de diferentes genótipos oriundos dos dois sistemas de cultivos, permite compreender o efeito das características intrínsecas dos genótipos e do sistema de cultivo sobre a qualidade dos grãos cozidos.…”
Section: Introductionunclassified
“…Varieties identical in these three traits may be grouped into one quality class based on these parameters but consumers easily distinguish a premium variety from a lower quality one (Champagne et al, 2010). This could lead to low rates of adoption of newly developed improved varieties by farmers.…”
Section: Future Directionsmentioning
confidence: 99%
“…To find adjectives for these other sensory properties, descriptive sensory profiling is employed; a trained sensory panel assesses food for aroma, texture, and flavour (Champagne et al, 2010). Comparisons by a trained panel between similar varieties (in terms of AC, GT) but classed as premium and second-best showed that slickness, roughness, and springiness were textural attributes that separated the two classes while sweet taste, popcorn flavour, and metallic mouthfeel were the flavour attributes (Champagne et al, 2010). Without phenotyping tools, these traits could not be associated with genetic loci.…”
Section: Future Directionsmentioning
confidence: 99%